Toxic effects of erythromycin, ciprofloxacin and sulfamethoxazole on photosynthetic apparatus in Selenastrum capricornutum - Liu, Bin-yang; Nie, Xiang-ping; Liu, Wei-qiu; Snoeijs, Pauline; Guan, Chao; Tsui, Martin T.K. (Ecotoxicology and environmental safety, 2011)
The effects of three antibiotics (erythromycin, ciprofloxacin and sulfamethoxazole) on photosynthesis process of Selenastrum capricornutum were investigated by determining a battery of parameters including photosynthetic rate, chlorophyll fluorescence, Hill reaction, and ribulose-1.5-bisphosphate carboxylase activity, etc. The results indicated that three antibiotics could significantly inhibit the physiological progress including primary photochemistry, electron transport, photophosphorylation and carbon assimilation. Erythromycin could induce acute toxic effects at the concentration of 0.06 mg L −1, while the same results were exhibited for ciprofloxacin and sulfamethoxazole at higher than 1.0 mg L −1. Erythromycin was considerably more toxic than ciprofloxacin and sulfamethoxazole and may pose a higher potential risk to the aquatic ecosystem. Some indices like chlorophyll fluorescence, Mg 2+-ATPase activity and RuBPCase activity showed a high specificity and sensitivity to the exposure of erythromycin, and may be potentially used as candidate biomarkers for the exposure of the macrolide antibiotics.